1979
DOI: 10.1039/c39790000707
|View full text |Cite
|
Sign up to set email alerts
|

A mixed valence binuclear complex of vanadium(IV) and vanadium(V). X-Ray crystal structure of (NH4)3[V2O3(nitrotriacetate)2]·3H2O

Abstract: A deep blue mixed valence complex v O ( n t a ) -O-VO(nta)]3-(nta = nitrilotriacetate) was found to be in equilibrium with wKvO(nta) (H20)]-and [Vv0,(nta)12in aqueous solution ; the crystal structure of its ammonium salt trihydrate has been determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
65
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 0 publications
8
65
1
Order By: Relevance
“…The UV-VIS spectra (Fig.1) of three V IV O-hpada complexes are similar to those of [VO(H 2 O)nta]¯[42][43][44] and its analogs[45] and are consistent with the tetragonally compressed symmetry commonly associated with spectra of the vanadyl ion and its complexes[45]. The results of elemental analysis agreed with a the complexes.…”
supporting
confidence: 79%
“…The UV-VIS spectra (Fig.1) of three V IV O-hpada complexes are similar to those of [VO(H 2 O)nta]¯[42][43][44] and its analogs[45] and are consistent with the tetragonally compressed symmetry commonly associated with spectra of the vanadyl ion and its complexes[45]. The results of elemental analysis agreed with a the complexes.…”
supporting
confidence: 79%
“…[29] The fact that only one sharp peak is observed supports the explanation that the two vanadyl groups are indistinguishable, and is consistent with the almost identical VϪO bond lengths (see Table 1). The VϭO(vanadyl) stretching vibration in mixedvalence vanadium(IV, V) is detected within the range of 947 cm Ϫ1 (see Nishizawa et al [30] ), 980 cm Ϫ1 (see Pessoa et al. [31] ) and 995 cm Ϫ1 (see Chakravarty et al [23] ), whereas the VϭO(vanadyl) stretching vibration of vanadium(IV) compounds is observed at 975 cm Ϫ1 and at 890Ϫ920 cm Ϫ1 for vanadium(V) compounds (see Nishizawa et al [30] ).…”
Section: Vibrational Spectroscopymentioning
confidence: 99%
“…The VϭO(vanadyl) stretching vibration in mixedvalence vanadium(IV, V) is detected within the range of 947 cm Ϫ1 (see Nishizawa et al [30] ), 980 cm Ϫ1 (see Pessoa et al. [31] ) and 995 cm Ϫ1 (see Chakravarty et al [23] ), whereas the VϭO(vanadyl) stretching vibration of vanadium(IV) compounds is observed at 975 cm Ϫ1 and at 890Ϫ920 cm Ϫ1 for vanadium(V) compounds (see Nishizawa et al [30] ). The strong peak at 794 cm Ϫ1 represents the combination mode consisting of the bending vibration δ OϪCϭO and the stretching vibration ν VϪO .…”
Section: Vibrational Spectroscopymentioning
confidence: 99%
“…It has been found that the anti linear configuration of the core facilitates a very effective overlap of the d xy metal orbitals through the oxo bridge p x orbital and, hence, a complete delocalization of the unpaired 3d electron over the two vanadium centers. [13,17,21] For an anti bent configuration, both localized and delocalized electronic structures are found. In these cases, the π basicity of the other coordinating atoms plays an important role in deciding the electronic structure.…”
mentioning
confidence: 94%
“…Structurally characterized complexes containing the {OV(µ-O)VO} 3+ core are very few. [13][14][15][16][17][18][19][20][21][22][23][24] In all these complexes, the metal ions are bridged by only the oxo group and they are symmetric with respect to the ligands bonded to them. Only in one case do the two ligands attached to the two metal centers differ in the substituents attached to them.…”
mentioning
confidence: 99%